(x+8)(x-122)=0

Simple and best practice solution for (x+8)(x-122)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+8)(x-122)=0 equation:


Simplifying
(x + 8)(x + -122) = 0

Reorder the terms:
(8 + x)(x + -122) = 0

Reorder the terms:
(8 + x)(-122 + x) = 0

Multiply (8 + x) * (-122 + x)
(8(-122 + x) + x(-122 + x)) = 0
((-122 * 8 + x * 8) + x(-122 + x)) = 0
((-976 + 8x) + x(-122 + x)) = 0
(-976 + 8x + (-122 * x + x * x)) = 0
(-976 + 8x + (-122x + x2)) = 0

Combine like terms: 8x + -122x = -114x
(-976 + -114x + x2) = 0

Solving
-976 + -114x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-8 + -1x)(122 + -1x) = 0

Subproblem 1

Set the factor '(-8 + -1x)' equal to zero and attempt to solve: Simplifying -8 + -1x = 0 Solving -8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 0 + 8 -1x = 0 + 8 Combine like terms: 0 + 8 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8

Subproblem 2

Set the factor '(122 + -1x)' equal to zero and attempt to solve: Simplifying 122 + -1x = 0 Solving 122 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-122' to each side of the equation. 122 + -122 + -1x = 0 + -122 Combine like terms: 122 + -122 = 0 0 + -1x = 0 + -122 -1x = 0 + -122 Combine like terms: 0 + -122 = -122 -1x = -122 Divide each side by '-1'. x = 122 Simplifying x = 122

Solution

x = {-8, 122}

See similar equations:

| (4/z-3)-24/z^2-9)=1 | | 20x^9-25x^7+15x^5-40x^4=0 | | -8x^2-20x+x^4=0 | | (14*​x^​7-​18*​x^​3)/(2x^​3) | | X+y=320 | | x^2+8x-122=0 | | 225=10(x-60)+75 | | 10x+21=15-21 | | (x^2)+(4x)+4=49 | | uy=-2/3x-2 | | 12x^2+7x+6=0 | | y=-30x+900 | | -8x^2-33+x^4=0 | | .52+.18s=3 | | 2x=6(x+5)-4 | | A/11=24/8 | | (y-3)/(y-2) | | 8(x+4)+7=10x-2(x-6) | | .52+.185=3 | | 6r-17=1+9r | | 5.32/1.4= | | y-3/y-2 | | (2x+6)+(3x+4)=90 | | -(x^2+x-2)= | | 8+4(4x-6)=5-4(2x+1) | | 5x^2-12x-65=0 | | 14*0.3= | | 2/3a^2b-1/6ab | | (2x-6)+(3x+4)=90 | | 4x^3+12x^2= | | y=(5x^2)-(2x)+3 | | 222+194+S=627 |

Equations solver categories